2006
DOI: 10.1196/annals.1374.066
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Rocky Mountain Spotted Fever Associated with a Novel Tick Vector, Rhipicephalus sanguineus, in Arizona, 2004

Abstract: This study describes preliminary results of an investigation of RMSF in Arizona associated with the brown dog tick, Rhipicephalus sanguineus. High numbers of dogs and heavy infestations of ticks created a situation leading to human disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 1 publication
1
22
0
4
Order By: Relevance
“…Both tick prevalence and abundance were highest at sites that had experienced the largest recent decreases in EVI, which is a proxy for overall vegetative cover and growth. Higher overall EVI values were associated with higher tick prevalence but lower tick abundance on dogs (Tables 4, 5) but we note that elevation was the single strongest predictor of tick occurrence among our sites and consistent with previous studies, we found higher tick abundance and prevalence on dogs at lower elevation sites ( Demma et al 2006;Okoli et al 2006). The relatively low infection rate with R. amblyommii in R. sanguineous (0.5%) and A. ovale (13%) is generally consistent with previously reported results in dog-derived ticks (Bermúdez et al 2009(Bermúdez et al , 2016.…”
Section: Discussionsupporting
confidence: 93%
“…Both tick prevalence and abundance were highest at sites that had experienced the largest recent decreases in EVI, which is a proxy for overall vegetative cover and growth. Higher overall EVI values were associated with higher tick prevalence but lower tick abundance on dogs (Tables 4, 5) but we note that elevation was the single strongest predictor of tick occurrence among our sites and consistent with previous studies, we found higher tick abundance and prevalence on dogs at lower elevation sites ( Demma et al 2006;Okoli et al 2006). The relatively low infection rate with R. amblyommii in R. sanguineous (0.5%) and A. ovale (13%) is generally consistent with previously reported results in dog-derived ticks (Bermúdez et al 2009(Bermúdez et al , 2016.…”
Section: Discussionsupporting
confidence: 93%
“…However, it can also be abundant in peridomestic areas, as reported in eastern Arizona [60,61]. They can be found walking on outside walls of houses, on the ground (between rocks), and inside cracks and crevices (Figure 8).…”
Section: Ecology Of Rhipicephalus Sanguineusmentioning
confidence: 79%
“…However, clinical studies have associated canine infection with B. v. berkhoffii and the presence of R. sanguineus ticks [50]. R. sanguineus is the most frequent urban tick in tropical regions, and its ability to feed on humans have been documented, including its role in a recent outbreak of Rocky Mountain Spotted Fever in humans in the United States [51].…”
Section: Discussionmentioning
confidence: 99%